Modulation of soy protein isolate gel properties by a novel "two-step" gelation process: Effects of pre-aggregation with different divalent sulfates. (15th November 2022) - Wang, Xufeng; Yu, Mengqin; Wang, Zhenzhong; Luo, Kaiyun; Adhikari, Benu; Miao, Song; Liu, Shutao
Highlights: Pre-aggregation markedly influenced the two-step gelation of soy protein isolate. Appropriate pre-aggregation promoted the formation of uniform gel structure. Over-aggregation resulted in coarser networks and weaker gels. ZnSO4 had a more pronounced effect than CaSO4 and MgSO4 at lower concentrations. The gel properties were significantly correlated with protein aggregate size. Abstract: A novel pre-aggregation process prior to gelation was applied to modulate the aggregation and gelation pathway of soy protein isolate (SPI). SPI dispersions were pre-aggregated with CaSO4, MgSO4 or ZnSO4 at 0–15 mM and then gelled by adding CaSO4 up to a final salt concentration of 35 mM. Compared with the sample without pre-aggregation, the storage modulus of SPI gels pre-aggregated with 10 mM CaSO4, 10 mM MgSO4, and 2.5 mM ZnSO4 were increased by 50.5%, 35.7%, and 63.6%, respectively. The fracture stress, texture profile analysis parameters, and water holding capacity were markedly improved by an appropriate level of pre-aggregation. To a certain extent, pre-aggregation could promote the formation of uniform structure with thicker strands, whereas over-aggregation resulted in a coarser network, which was correlated with the volume-mean diameter (D4, 3 ) of pre-aggregated SPI particles. The results are of great value for further understanding of gelation mechanism of proteins.